Catalytic processes for conversion of natural gas engine exhaust and 2,3-butanediol conversion to 1,3-butadiene - Zeng, Fan (Kansas State University, 2016)
Extensive research has gone into developing and modeling the three-way catalyst (TWC) to reduce the emissions of hydrocarbons, NOx and CO from gasoline-fueled engines level. However, much less has been done to model the use of the three-way catalyst to treat exhaust from natural gas-fueled engines. Our research address this gap in the literature by developing a detailed surface reaction mechanism for platinum based on elementary-step reactions. A reaction mechanism consisting of 24 species and 115 elementary reactions was constructed from literature values. All reaction parameters were used as found in the literature sources except for steps modified to improve the model fit to the experimental data. The TWC was simulated as a one-dimension, isothermal plug flow reactor (PFR) for the steady state condition and a continuous stirred-tank reactor (CSTR) for the dithering condition. This work describes a method to quantitatively simulate the natural gas engine TWC converter performance, providing a deep understanding of the surface chemistry in the converter. Due to the depletion of petroleum oil and recent volatility in price, synthesizing value-added chemicals from biomass-derived materials has attracted extensive attention. 1, 3-butadiene (BD), an important intermediate to produce rubber, is conventionally produced from petroleum. Recently, one potential route is to produce BD by dehydration of 2, 3-butanediol (BDO), which is produced at high yield from biomass. This reaction was studied over two commercial forms of alumina. Our results indicate acid/base properties greatly impact the BD selectivity. Trimethylamine can also modify the acid/base properties on alumina surface and affect the BD selectivity. Scandium oxide, acidic oxide or zirconia dual bed systems are also studied and our results show that acidic oxide used as the second bed catalyst can promote the formation of BD, while 2,5-dimethylphenol is found when the zirconia is used as the second bed catalyst which is due to the strong basic sites.
Keywords: Natural gas engine; Three-way catalytic converter modeling; Methane oxidation; 2, 3-butanediol biomass conversion and dehydration